Economic Potential of Renewable Energy with a Financial Feasibility Approach in Kupang, NTT - Achmad Factur Rahman; I Nyoman Gita Indrawan (Jurnal Indonesia Sosial Teknologi, 2024)
The use of biomass as fuel at PLTU Bolok can reduce emissions, save basic costs for providing electricity and increase fuel alternative competitiveness for PLN. A lot of unproductive vacant land can now be used to plant calliandra trees and used for cofiring, the use of woodchip biomass for cofiring PLTUs can also build a community economy. This research aims to analyze the feasibility of investment using a financial aspect approach in the biomass procurement program in Kupang, NTT. This business feasibility analysis was carried out to find out whether the biomass development plan was feasible from a financial aspect. This research will analyze the Net Present Value (NPV), Net Benefit Cost Ratio (BCR), and Payback Period values for the business.